Tissue-Specific Expression of Circ_015343 and Its Inhibitory Effect on Mammary Epithelial Cells in Sheep - Wu, Xinmiao; Zhen, Huimin; Liu, Yan; Li, Lu; Luo, Yuzhu; Liu, Xiu; Li, Shaobin; Hao, Zhiyun; Li, Mingna; Hu, Liyan; Qiao, Lirong; Wang, Jiqing (Frontiers in Veterinary Science, 2022)
Circular RNAs (circRNAs) are a kind of non-coding RNA that have an important molecular function in mammary gland development and lactation of mammals. In our previous study, circ_015343 was found to be highly expressed in the ovine mammary gland tissue at the peak-lactation period by using RNA sequencing (RNA-seq). In the present study, the authenticity of circ_015343 was confirmed by using reverse transcriptase-polymerase chain reaction (RT-PCR) analysis and Sanger sequencing. The circ_015343 was derived from the complete 10 exons of aminoadipic semialdehyde synthase (AASS), ranging from exon 2 to exon 11 and mainly located in cytoplasm of ovine mammary epithelial cells. The circRNA was found to be expressed in eight ovine tissues, with the highest expression level in the mammary gland and the least expression in Longissimus dorsi muscle. The circ_015343 had a lower level of expression in a sheep breed with higher milk yield and milk fat content. The disturbed circ_015343 increased the viability and proliferation of the ovine mammary epithelial cells. The inhibition of circ_015343 also increased the expression levels of three milk fat synthesis marker genes: acetyl-coenzyme A carboxylase alpha (ACACA), fatty acid-binding protein 4 (FABP4), and sterol regulatory element-binding protein 1 (SREBP1), as well as three proliferation-related genes: cyclin dependent kinase 2 (CDK2), cyclin dependent kinase 4 (CDK4) and proliferating cell nuclear antigen (PCNA), but decreased the expression level of its parent gene AASS. A circRNA-miRNA-mRNA interaction network showed that circ_015343 would bind some microRNAs (miRNAs) to regulate the expression of functional genes related to the development of mammary gland and lactation. This study contributes to a better understanding of the roles of circ_015343 in the mammary gland of sheep.